2023
DOI: 10.1038/s41598-023-36704-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gut microbiota in patients with Williams–Beuren Syndrome reveals dysbiosis linked to clinical manifestations

Federica Del Chierico,
Valeria Marzano,
Matteo Scanu
et al.

Abstract: Williams–Beuren syndrome (WBS) is a multisystem genetic disease caused by the deletion of a region of 1.5–1.8 Mb on chromosome 7q11.23. The elastin gene seems to account for several comorbidities and distinct clinical features such including cardiovascular disease, connective tissue abnormalities, growth retardation, and gastrointestinal (GI) symptoms. Increasing evidence points to alterations in gut microbiota composition as a primary or secondary cause of some GI or extra-intestinal characteristics. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…has been already negatively associated with metabolic risk 35 . Reduction of Firmicutes was also evidenced in WBSs patients by metataxonomy 19 . Anyway, metaproteomic results were not completely overlapping to that obtained by the previous cited 16S rRNA-based metagenomic study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…has been already negatively associated with metabolic risk 35 . Reduction of Firmicutes was also evidenced in WBSs patients by metataxonomy 19 . Anyway, metaproteomic results were not completely overlapping to that obtained by the previous cited 16S rRNA-based metagenomic study.…”
Section: Discussionmentioning
confidence: 81%
“…This evidence led us to speculate a major role of the WBS disease phenotype in the shaping of the GM functional signatures, compared to age dependency. Indeed, a previous 16S rRNA-based metagenomic study revealed the absence of statistically significant differences amongst age for the WBS group excluding the variable age as confounding factor, and provided interesting results comparing the WBSs to age-matched healthy subjects 19 . Therefore, we proceeded by analyzing all WBS samples and comparing them to the CTRL group, regardless of age, to establish a comprehensive understanding of the WBS impact on GM functionality.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, our study demonstrated that SADI-S significantly increased the abundance of the phylum Verrucomicrobiota. Akkermansia , belonging to the phylum Verrucomicrobia, is an anti-inflammatory bacteria ( Luo et al, 2022 ; Del Chierico et al, 2023 ), and its abundance is negatively correlated with the level of insulin resistance ( Dao et al, 2016 ; Plovier et al, 2017 ; Konturek et al, 2018 ). We also found that the abundance of Akkermansia was significantly increased after SADI-S, concomitant with the significant improvement of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Coriobacteriaceae may play a vital role in bariatric surgery regulating host glucose homeostasis. Bifidobacterium , belonging to the phylum Actinomycetota, is also an anti-inflammatory bacteria ( Luo et al, 2022 ; Del Chierico et al, 2023 ). The abundance of Bifidobacterium decreases in patients with T2D and increases with BPD/DS and duodenal jejunal bypass ( Mukorako et al, 2019 ; Yu et al, 2020 ), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%